Efektivitas G-Form Sebagai Media Evaluasi Dalam Pendidikan Agama Islam - Anggi Pratiwi; Hanifah Salsabila, Unik; Fitri Rahmadani; Friska Amalia Fahra; An Nisaa Zukhrufatul Jannah (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
The development of the times in the era of globalization requires that we always update on increasingly sophisticated technology, including for the teaching and learning process. One technique for evaluating student achievement using technology is the survey method with Google Forms. The use of the Google form aims to make it easier for students and educators to access evaluations of students' teaching and learning achievements. This study uses the literature study method and data collection techniques obtained from articles, books, and other validated sources. The results of this study explain that evaluation in the teaching and learning process using the Google form in Islamic religious education lessons makes it easier for educators, especially during the Covid-19 pandemic. The use of Google forms which is very easy to access makes educators and students have no difficulties in using it. From this article it is hoped that it will provide educators with views on the use of Google Forms in evaluating the achievements of students during the learning process. Keywords: Google Forms; Learning Evaluation; Islamic education